OLOS: OPTIMALISASI LOT SIZING PADA SISTEM MRP UNTUK MEMINIMUMKAN BIAYA PERSEDIAAN BAHAN BAKU DI CV. ICHA COLLECTION. - Eko Wandiro; Saufik Luthfianto (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2019)
CV. Icha Collection Pemalang is an industry engaged in the manufacture of bags and wallets. For the manufacture of bags in particular is the LC Type Women's Bags. The problem in this study that arises is the supply of raw materials. Raw material inventory is where there is a delay in the delivery of raw materials in the case of an expedition. This study aims to plan the supply of raw materials at an efficient cost so that raw material needs do not experience obstacles. This research will discuss the planning of LC Bag Type OL with raw material (optimization of lot sizing) on the MRP system. The analysis technique used is plotting past request data, forecasting the future, and MRP. The results of this study are the application of the Lot Sizing method, Part Balancing Period for each raw material for Women Bags Type LC in CV. Icha Collection Pemalang can minimize the total cost of inventory. The Part Balancing Period method has the lowest total inventory cost for each raw material and optimizes 91.33% of raw material inventory. CV. Icha Collection Pemalang merupakan indusri yang bergerak di bidang pembuatan tas dan dompet, khususnya Tas Wanita Type LC. Permasalahan dalam penelitian ini adalah persediaan bahan baku, dimana terjadi keterlambatan pengiriman bahan baku dalam hal ekspedisi. Penelitian ini bertujuan untuk merencanakan persediaan bahan baku dengan biaya yang efisien sehingga kebutuhan bahan baku tidak mengalami kendala. Penelitian ini akan membahas perencanaan bahan baku Tas Wanita Type LC dengan OLOS (optimalisasi lot sizing) pada sistem MRP. Teknik analisis yang dilakukan yaitu mengeplot data pemintaan masa lalu, peramalan, dan MRP. Hasil dari penelitian ini adalah penerapan metode Lot Sizing, Part Periode Balancing untuk setiap bahan baku Tas Wanita Type LC di CV. Icha Collection Pemalang dapat meminimalkan biaya total persediaan. Metode Part Periode Balancing mempunyai total biaya persediaan paling rendah untuk setiap bahan bakunya dan mengoptimalkan 91,33% persediaan bahan baku.